Reduced integrity of sensorimotor projections traversing the posterior limb of the internal capsule in children with congenital hemiparesis - Tsao, H.; Pannek, K.; Fiori, S.; Boyd, Roslyn; Rose, S. (2014)
There is reduced integrity of corticospinal projections that traverse the posterior limb of the internal capsule (PLIC) in children with unilateral cerebral palsy (CP). It remains unclear whether there are changes in integrity of other projections traversing the PLIC. Forty children with congenital hemiparesis and 15 typically developing children underwent structural and diffusion-weighted MRI. All children with congenital hemiparesis showed lesions to the periventricular white matter. Structural images were parcellated into 34 cortical regions per hemisphere and posterior limb of the internal capsule was identified. PLIC connections to each cortical region were extracted using probabilistic tractography. Differences between hemispheres for each cortical projection (asymmetry index (AI)) and tract microstructure (fractional anisotropy (FA), mean diffusivity (MD)) were assessed. The results showed that 17 children (42.5%) with congenital hemiparesis showed bilateral lesions on structural MRI. Projections to the primary motor cortex (precentral gyrus and paracentral lobule) showed greater asymmetry in unilateral CP group compared to typically developing children and indicate reduced projections on the hemisphere contralateral to the impaired limb (i.e., contralateral hemisphere). Reduced FA and increased MD were also observed for connections with the primary motor cortex, primary sensory cortex (postcentral gyrus) and precuneus on the contralateral hemisphere in children with congenital hemiparesis. Similar changes were observed between children with unilateral and bilateral lesions on structural MRI. Notably, microstructural changes were associated with deficits in both sensory and motor function. The findings further unravel the underlying neuroanatomical correlates of sensorimotor deficits in children with congenital hemiparesis. © 2013 Elsevier Ltd.